Application of wavelet decomposition in volcanic seismic data. (April 2020) - Dairoh,; Suryanto, W
Abstract: Volcanic data is in the form of broadband data that a wide range of frequencies and contains a high level of noise. So that the noise decomposition process must be chosen correctly, it is intended that the volcanic seismic recording data containing event information contained there is not decomposed. For This reason, noise decomposition has been carried out by applying the wavelet process, namely by using wavelet decomposition on the recording data at the Wanagama station during the Merapi volcano eruption 2010. This Decomposition of noise uses Daubechies db 5 level 5 detail 1 wavelet decomposition. Level 5 detail 1 is able to decompose noise well a volcanic event are obtained during the eruption. One of them is the event of deep volcanic event (VT-A), shallow volcanic earthquake (VT-B) and pyroclastic flows that occurred during Merapi eruption on October 26, 2010 and November 3, 2010.